The Taxonomy, Distribution, And Status of Philippine Wild Pigs - Oliver, William L. R. (Silliman Journal, 2024)
Recent taxonomic reviews have revealed that there are three species and at least two subspecies of wild pigs in the Philippines, of which two species and one subspecies are endemic. This is a larger number of endemic suid taxa than any other country, with the exception of Indonesia. Unfortunately, however, the generally extreme levels of deforestation on most islands on which they occur, coupled with intense hunting pressure, inadequate legal protection, and the poor enforcement of existing legislation even within protected areas, have resulted in the systematic decline of all Philippine populations of these animals: These factors are especially apparent in the Visayan region, where the endemic warty pig, S. cebifrons, is probably the second most endangered of the world’s suids. This species is now extinct or close to extinction in five (Masbate, Guimaras, Cebu, Siquijor and Bohol) of the seven is- lands in which it is known or believed to have occurred, and now survives only in a few small, isolated areas of Negros and Panay, where all remaining populations are declining as a result of continued habitat destruction and intense hunting pressure. By comparison, the other two species. of Philippine pigs -- S. philippensis of Luzon, Samar, Leyte, Mindanao and associated smaller islands, and S. barbatus Muller of Balabac, Palawan, the Calamian Islands (S. b. ahoenobarbus) and Tawi-tawi and Sibutu (S. 6. barbatus) remain rather more widely distributed throughout their ranges at the present time.